Urban housing prices, female labor participation, and economic development in china: A theoretical and empirical analysis - Li, Yuan; Khan, Jamal; Mahsud, Qaiser Jamal (Frontiers in Psychology, 2023)
China's housing distribution system has changed dramatically, and the country's housing markets have seen rapid price appreciation. However, the extent to which urban housing prices influence female labor participation (FLP) in labor decision-making, as well as how the FLP rate influences economic development, has not been sufficiently investigated. Accordingly, we first build a theoretical neoclassical economic development model that includes housing consumption factors to estimate the effect of housing price dynamics on FLP. We then use the 2017 China Family Panel Studies (CFPS) database to empirically estimate the intrinsic relationship between urban housing prices, FLP and economic development through the lens of the balanced growth path, and we come up with four main findings. First, the theoretical model demonstrates that rising housing prices result in an increase in FLP, which stimulate economic development. More interestingly, an excessive increase in housing prices will undermine women’s ability to drive economic development. Second, the empirical evidence shows that a unit increase in housing prices results in a 0.186% of increase in the probability of FLP. Third, housing prices have varying effects on economic development in China’s Eastern, Central, and Northeast regions. Finally, the threshold model shows that is FLP positively influence economic development until the housing price logarithm reaches 8.8134, after which FLP's beneficial effect on economic development efficiency will be hampered.